Bibliometric Analysis of Proceedings of the Paksitan Academy of Sciences: Part A from 2016 to 2022: A Short Bibliometric Note from 2016 to 2022 - Hassan, Waseem (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2022)
Since 2016, Scopus database is directly covering Proceedings of the Pakistan Academy of Sciences (PPAS): Part A. Till 28th April, 2022 it has published 190 research documents majorly comprising of articles (n=126), book chapters (n=42), conference papers (n=16) and reviews (n=6). PPAS-A publishes in the areas of computer science, materials science, physics and astronomy, engineering sciences, chemistry, statistics, mathematics, geography, and geology. The entire publication data was downloaded from Scopus and analyzed on R-Studio (Bibliometrix/ Biblioshiny). In all publication, 210 authors from 377 departments or institutes (or more precisely 192 universities) from 12 Asian, 11 European, 4 Middle East, 1 Oceanic (New Zealand), 1 North American (USA), and 3 African countries have contributed (Figure 1). The lists of all authors (with total publications (TP), total citations (TC), publications years, h-index, g-index and m-index), all universities (with TP) and countries (with TP) are provided in supplementary table 1. All publications (n=190) received 174 total citations with 6 h-index. Similarly for 2021 the Citescore, SJR and SNIP were found to be to 0.4, 0.161 and 0.367, respectively. In a short span of only six years, it has achieved considerable rankings in general computer science (193/226), general physics and astronomy (200/233) and general materials sciences (402/455). The success could be attributed to the entire editorial board, reviewers, and authors around the world.